Piranti Perencanaan dan Pengawasan Mutu dalam Manajemen Proyek Sistem Informasi - Ratnaningsih AW (Universitas Budi Luhur, 2011)
In an information system development contract, hand over of the system is usually followed by a maintenance periode. The need of system maintenance how small the work is to be done, is due to the less fulfillment of the system requirements. In the case of system scope and requirements are well defined, a proper tool for achieving the required quality could be used during the planning and controlling phase. This paper presents a tool to support achieving the required quality of an information system project product for non financial and time aspectsKeyword: information system project, quality management